2014
DOI: 10.1111/wvn.12065
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Communication Between Parents and Nurses of Hospitalized Technology‐Dependent Children

Abstract: The results of this integrative review inform our understanding of the parent-nurse communication process. The findings provide nurses with an understanding of strategies to better engage in respectful, engaging, and intentional communication with parents of hospitalized technology-dependent children and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…This study is viewed with caution due to the small sample size and low survey return rate of 10.2% ( n = 134 of 1320 surveys sent out) which limits the generalisability of the results (Uhl et al, 2013). Other single setting studies on partnership nursing with parents of children with long‐term conditions found that parents expected to be treated as experts in the care of their own children (Baird et al, 2016; Giambra, Stiffler, et al, 2014). Baird et al (2016) explored partnership nursing with parents of children with long‐term conditions in a single paediatric intensive care unit in the USA and found that parents reported inconsistencies in the continuity of care of their child which created issues of distrust, as some nurses provided greater insight into their child's medical diagnosis and care requirements compared to other nurses.…”
Section: Introductionmentioning
confidence: 99%
“…This study is viewed with caution due to the small sample size and low survey return rate of 10.2% ( n = 134 of 1320 surveys sent out) which limits the generalisability of the results (Uhl et al, 2013). Other single setting studies on partnership nursing with parents of children with long‐term conditions found that parents expected to be treated as experts in the care of their own children (Baird et al, 2016; Giambra, Stiffler, et al, 2014). Baird et al (2016) explored partnership nursing with parents of children with long‐term conditions in a single paediatric intensive care unit in the USA and found that parents reported inconsistencies in the continuity of care of their child which created issues of distrust, as some nurses provided greater insight into their child's medical diagnosis and care requirements compared to other nurses.…”
Section: Introductionmentioning
confidence: 99%
“…It can be regarded as a crisis event for children because of its numerous related stressors, such as isolation from the family and significant others, loss of control, and exposure to unfamiliar environments (Agostini et al., ; Foster, Whitehead, & Maybee, ; Kools et al., ; Tallen, Kendall, & Snider, ). For these reasons, including the parents in the nursing care of their children is beneficial to both the child and parents (Giambra, Stiffler, & Broome, ; Power & Franck, ).…”
mentioning
confidence: 99%
“…2000-2014 yılları arasında yapılan çalışmaların incelendiği bir sistematik derlemede, hastanede yatan, teknolojiye bağımlı çocukların ebeveynlerinin hemşirelerle olan iletişiminin önemli olduğu ve ailelerin bakım becerilerini görerek öğrenmek istedikleri açıklanmıştır. 29 Ayrıca sosyal hizmet uzmanları evde uzun süreli süreğen bir bakım sağlamanın yarattığı stresle başa çıkmaları konusunda aileye yardımcı olabilir. 5,10,19 Bakım sürecindeki ihtiyaçlarının saptanmasında ilk adım ailelerin hedeflerinin belirlenmesidir.…”
Section: Teknoloji Bağımlı çOcukların Evde Hemşirelik Bakımıunclassified